The meaning of the EPSRC principles of robotics - Joanna J. Bryson (Connection Science)
In revisiting the Principles of Robotics (as we do in this special issue), it is important to carefully consider their full meaning – their history, the intentions behind them, and their actual societal impact to date. Here I address first the meaning of the document as a whole, then of its constituent parts. Further, I describe the nature of policy, and use the Principles as a case study to discuss how government and academia can interact in constructing policy. I defend the Principles and their main themes: that commercially manufactured robots should not be responsible parties under the law, and that users should not be deceived about robots' capacities or moral status. This perspective allows for the incorporation of robots immediately into UK society and law – the objective of the Principles. The Principles were not designed for every conceivable robot, but rather serve in part as design specifications for robots to be incorporated as legal products into British society.